ECONOMIC EVALUATION OF THE EFFECT OF THE APPLICATION OF BIOSTIMULANTS ON SPRING RAPE AND OATS - Angel SAROV; Krasimir KOSTENAROV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The effect of the application of biostimulants in agricultural crops has not been fully studied and evaluated from an economic aspect. The purpose of the research is to assess the economic efficiency of the application of biostimulants in the organic production of spring rapeseed and oats. 2-year field trials were conducted using a block method with foliar treatment with Chitosan, Vermicomposting and nature-identical growth regulator in 2 phenological stages. The biological response of the crops at different doses of the biostimulants was investigated. The obtained primary results were used as input data for the construction of an economic-mathematical model for economic evaluation. In a methodological aspect, linear modeling is applied in order to optimize the production structure of a selected agricultural holding. It is concluded that biostimulants have a positive effect on yield and biometrics of treated crops, but the complex economic effect on farm profit is organic.